PANORAMA OF FLORICULTURE AND PHYSIOLOGICAL ASPECTS OF AMARYLLIS UNDER WATER STRESS CONDITIONS - Martins, Lady Daiane Costa de Sousa; dos Santos, Wagner Martins; Jardim, Alexandre Maniçoba da Rosa Ferraz; Souza, Jheizon Feitoza do Nascimento; de Lima e Silva, Lara Rosa; de Souza, Pedro Paulo Santos; de Moura, Márcia Bruna Marim; de Souza, Klébia Raiane Siqueira; da Silva, Elania Freire; da Silva, Thieres George Freire; de Souza, Luciana Sandra Bastos; Simões, Adriano Nascimento (Editora Impacto Científico, 2025)
Floriculture is one of the most promising segments of global agribusiness, characterized by high profitability and continuous expansion, especially in countries such as the Netherlands, China, and the United States. In Brazil, the sector has stood out for its steady growth, even in the face of economic and climatic adversities, generating billions of reais and thousands of direct and indirect jobs. Among the species of greatest commercial relevance, amaryllis (Hippeastrum hybridum Hort.) presents significant economic and ornamental potential due to its wide diversity of cultivars, high market demand, and good adaptability to tropical and subtropical conditions. However, environmental factors, particularly water availability, significantly affect the productivity and quality of this species’ flowers and bulbs. Water stress induces physiological and biochemical changes, such as stomatal closure, reduced photosynthetic rate, and accumulation of reactive oxygen species, compromising cellular metabolism and the visual appearance of the plants. To minimize these effects, amaryllis exhibits adaptive responses associated with increased activity of antioxidant enzymes and structural modifications in leaf tissues. This review presents an updated overview of the flower agribusiness, emphasizing the economic importance and edaphoclimatic requirements of amaryllis, and discusses the main physiological mechanisms involved in the response to water deficit. Understanding these responses is essential for the development of more efficient and sustainable water management practices, contributing to the production of higher-quality flowers and to strengthening the competitive performance of Brazilian floriculture.DOI: https://doi.org/10.56238/edimpacto2025.085-004